Recycling method of waste titanium mesh lead dioxide anode plate

Through ultrasonic cleaning of dilute sulfuric acid and electrochemical deplating, waste titanium mesh lead dioxide anode plate is treated, combined with the conversion and electrodeposition technology of lead dioxide, the problems of complex recycling process and low pass rate of waste plates are solved, and the effect of efficient recycling and high-quality reuse is achieved.

CN119736651APending Publication Date: 2025-04-01KUNMING UNIV OF SCI & TECH +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411927607.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the prior art, the recycling process of waste titanium mesh lead dioxide anode plates is complex, the product pass rate is low, and the electrochemical deplating process has problems such as serious corrosion, high labor intensity and low working efficiency of the workpiece substrate.

Method used

After ultrasonic cleaning with dilute sulfuric acid, titanium mesh plates without lead dioxide were obtained by electrochemical deplating, and then the lead dioxide was converted into lead oxide and added to the lead nitrate solution. After purification, the basic plating solution was obtained, and then lead dioxide was deposited on the bottom layer titanium mesh plate by electrodeposition technology.

Benefits of technology

The efficient recycling and utilization of waste titanium mesh lead dioxide anode plate is achieved, with a recovery rate of more than 92%. The active layer of lead dioxide on the reelected titanium mesh lead dioxide anode plate is dense, has no pores, has a long service life of the plate and low trough voltage.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a recycling method of a waste titanium mesh lead dioxide anode plate, and belongs to the technical field of comprehensive recycling of hydrometallurgy. The method comprises the following steps: ultrasonically cleaning a waste titanium mesh lead dioxide anode plate with dilute sulfuric acid, carrying out electrochemical deplating and stripping to obtain a titanium mesh plate without lead dioxide, lead dioxide particles and a lead nitrate solution, reassembling and coating the titanium mesh plate to prepare a titanium mesh plate containing a bottom layer, converting lead dioxide into lead oxide, adding the lead oxide into the lead nitrate solution, and preparing the titanium mesh plate containing the bottom layer. And copper nitrate and dilute nitric acid are added into the basic plating solution to obtain a lead nitrate plating solution, and the titanium mesh plate containing the bottom layer is placed in the lead nitrate plating solution to be subjected to electro-deposition to obtain the titanium mesh lead dioxide anode plate. According to the method, the recovery rate reaches 92% or above, the lead dioxide active layer on the re-electrodeposited titanium mesh lead dioxide anode plate is compact and free of pores, the service life of the electrode plate is long, and the cell voltage is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for recycling waste titanium mesh lead dioxide anode plates, belonging to the technical field of comprehensive recycling of hydrometallurgy. Background Art

[0002] Lead dioxide electrodes are used as insoluble electrodes in the electrolysis industry. When electrolyzed in sulfuric acid, they have high oxygen evolution overpotential, strong oxidation ability, good corrosion resistance, good conductivity, and can pass large currents. However, they have poor mechanical strength and are brittle. The selection of matrix materials is particularly important. Commonly used matrix materials include ceramics, carbon materials, stainless steel, and various metal materials. Titanium stands out from many matrix materials because it is a valve-type metal, has strong corrosion resistance, is not easy to deform, and has a thermal expansion coefficient similar to that of lead dioxide. Researchers believe that it is an ideal matrix material for lead dioxide electrodes.

[0003] The main reason why the PbO2 layer is brittle and easy to peel off is that the internal stress generated by the electrodeposition of β-PbO2 causes cracks in the coating, and β-PbO2 cannot be firmly bonded to the substrate. In addition, a high-resistance layer of TiO2 will be formed between the active layer and the substrate, which will passivate the titanium substrate, making it difficult to conduct electricity, increasing the anode potential, and its use value will soon be lost. In order to ensure good bonding between the surface active coating titanium and the substrate and maintain good conductivity and high corrosion resistance, a new lead dioxide electrode has been developed. The new lead dioxide electrode mainly combines an anti-passivation bottom layer between the titanium substrate and the β-PbO2 coating, such as platinum group metals and their oxides, silver and lead-silver alloys, tin-antimony oxides, and titanium-tantalum composite oxides as the bottom layer. The method for making this new titanium-based lead dioxide electrode is: first, an intermediate layer is prepared on the titanium substrate by brushing, sintering, etc., and then electrodeposited.

[0004] There are problems of unstable process and low product qualification rate in the production process or the re-production of waste boards. For coatings that do not meet the quality requirements, if they are re-plated on them, the bonding between the coating and the substrate will be poor, the coating will peel off, etc. Therefore, the unqualified coating must be removed. Generally, chemical stripping is used. In actual production, the workpiece to be treated needs to react in a boiling treatment solution for 2-3 hours before lead dioxide can be completely stripped. In addition, there is the problem of serious corrosion of the workpiece substrate. In addition, this production method has high labor intensity, low work efficiency, and incomplete stripping. The electrochemical stripping coating will also be damaged, and the subsequent electroplating interface resistance will be large and the tank voltage will be high. Summary of the invention

[0005] Aiming at the problems of complex process and low product qualification rate in recycling of waste titanium mesh lead dioxide anode plates, the present invention proposes a recycling method for waste titanium mesh lead dioxide anode plates, wherein the waste titanium mesh lead dioxide anode plates are ultrasonically cleaned with dilute sulfuric acid, stripped by electrochemical stripping to obtain titanium mesh plates without lead dioxide, lead dioxide particles and lead nitrate solution, the titanium mesh plates are reassembled and coated to prepare titanium mesh plates containing a bottom layer, the lead dioxide is converted into lead oxide and then added to the lead nitrate solution, purified to obtain a basic plating solution, copper nitrate and dilute nitric acid are added to the basic plating solution to obtain a lead nitrate plating solution, and the titanium mesh plates containing a bottom layer are placed in the lead nitrate plating solution for electroplating to obtain titanium mesh lead dioxide anode plates. The recovery rate of the method of the present invention reaches more than 92%, the lead dioxide active layer on the re-electrodeposited titanium mesh lead dioxide anode plates is dense and pore-free, the plate has a long service life, and the cell voltage is low.

[0006] A method for recycling waste titanium mesh lead dioxide anode plates, the specific steps are as follows:

[0007] (1) Pretreatment of waste anode plates: The waste titanium mesh lead dioxide anode plates are ultrasonically cleaned with dilute sulfuric acid to obtain pretreated waste titanium mesh lead dioxide anode plates;

[0008] (2) Electrochemical stripping of lead dioxide: using the waste titanium mesh lead dioxide anode plate from step (1) as the anode and the aluminum plate as the cathode, placing them in a nitric acid electrolyte, and electrochemically stripping them for 1 to 6 hours at a temperature of 25 to 40° C., under ultrasonic and mechanical stirring conditions to obtain a titanium mesh plate free of lead dioxide, lead dioxide particles and lead nitrate solution; the nitric acid electrolyte contains HNO3, Ce(NO3)3, hydrogen peroxide, vitrified microspheres and silicon carbide micropowder;

[0009] (3) Re-coating and assembling the titanium mesh: The titanium mesh that does not contain lead dioxide in step (2) is washed with hot alkali, and then divided and separated into the titanium mesh, titanium conductive reinforcement ribs and titanium copper-clad conductive beams. The titanium mesh is sandblasted, pickled, washed with deionized water and dried to obtain a pre-treated titanium mesh. The pre-treated titanium mesh is evenly coated with a precursor liquid, dried and sintered. The coating-drying-sintering process is repeated 3 to 8 times, and baked for 1 to 2 hours to obtain a titanium mesh bottom layer. The titanium mesh bottom layer is assembled and welded with the titanium conductive reinforcement ribs and the titanium copper-clad conductive beams to obtain a titanium mesh plate containing a bottom layer. The solvent of the precursor liquid is n-butanol, and it contains stannous chloride, antimony chloride, cerium chloride, calcium chloride and dilute hydrochloric acid.

[0010] (4) Conversion of lead dioxide into lead oxide: the lead dioxide particles in step (2) are wet-milled to a particle size of 400 to 2000 mesh, dried to obtain lead dioxide powder, the lead dioxide powder is uniformly mixed with citric acid and hydrogen peroxide solution and reacted to obtain lead citrate, and the lead citrate is calcined and decomposed to obtain lead oxide;

[0011] (5) Purification of lead nitrate solution: dissolving the lead oxide obtained in step (4) in the lead nitrate solution obtained in step (2), adding hydrogen peroxide, adjusting the pH value to 1-3 with sodium hydroxide and precipitating, separating the solid from the liquid, adding Na2S to the filtrate for reaction, separating the solid from the liquid to obtain a base plating solution, adding copper nitrate to the base plating solution, and adjusting the pH value to 1-2 with dilute nitric acid to obtain a lead nitrate plating solution;

[0012] (6) Electrodeposition of lead dioxide: placing the titanium mesh plate containing the bottom layer in step (3) in the lead nitrate plating solution in step (5), and electroplating at a temperature of 50 to 80° C. for 3 to 8 hours to obtain a titanium mesh lead dioxide anode plate.

[0013] Preferably, the concentration of the dilute sulfuric acid in step (1) is 10 to 30 wt.%.

[0014] Preferably, in the nitric acid electrolyte of step (2), HNO3 comprises 150-350 g / L, Ce(NO3)3 comprises 1-5 g / L, 30 wt.% hydrogen peroxide comprises 30-100 ml / L, glass microspheres comprise 5-10 g / L, and silicon carbide micropowder comprises 5-10 g / L.

[0015] Preferably, the current density of the electrochemical stripping in step (2) is 5 to 30 A / dm 2 .

[0016] Preferably, the washing liquid for hot alkali washing in step (3) is a KNO3-KOH mixed solution, the KNO3 concentration in the KNO3-KOH mixed solution is 5-10wt.%, the KOH concentration is 5-10wt.%, the hot alkali washing temperature is 250-400°C, and the time is 3-5min;

[0017] The pickling solution is an oxalic acid solution, the concentration of the oxalic acid solution is 10-20wt.%, and the pickling temperature is 80-100°C;

[0018] Taking the total molar amount of stannous chloride, antimony chloride, cerium chloride and calcium chloride in the precursor liquid as 100, stannous chloride is 72-90, antimony chloride is 5-15, cerium chloride is 3-9, and calcium chloride is 2-4; the amount of dilute hydrochloric acid added to the precursor liquid is 20-40 ml / L;

[0019] The sintering temperature is 400-600°C for each time, and the time is 5-10 minutes; the roasting temperature is 400-600°C.

[0020] Preferably, in step (4), the molar ratio of lead dioxide powder, citric acid and hydrogen peroxide solution is (20-40):(10-20):(40-70).

[0021] Preferably, the calcination decomposition temperature in step (4) is 300-500° C. and the time is 1-3 hours.

[0022] Preferably, in step (5), the amount of hydrogen peroxide added is 3-7 ml / L, and the amount of Na2S added is 1-3 g / L.

[0023] Preferably, in the lead nitrate plating solution of step (5), the content of lead nitrate is 200-350 g / L, copper nitrate is 0.1-10 g / L, nitric acid is 5-15 g / L, and sodium fluoride is 0.05-0.5 g / L.

[0024] Preferably, the anode current density of the electrodeposition in step (6) is 100 to 500 A / dm 2 .

[0025] The beneficial effects of the present invention are:

[0026] (1) The titanium mesh lead dioxide anode plate obtained by recycling and reusing the waste titanium mesh lead dioxide anode plate of the present invention has good electrode conductivity, low cell voltage during electrolysis, and a recovery rate of more than 85%. The lead dioxide redeposited on the waste plate is dense and has no pores, and the plate has a long service life;

[0027] (2) The present invention uses Ce(NO3)3 in the electrochemical stripping step of lead dioxide, utilizing its strong oxidizing property to accelerate the stripping of lead dioxide;

[0028] (3) The present invention uses vitrified microspheres and silicon carbide micropowder in the electrochemical stripping step of lead dioxide so that particles are doped into the defects of lead dioxide under ultrasonic conditions to accelerate the shedding of lead dioxide;

[0029] (4) In the step of converting lead dioxide into lead oxide, the present invention uses lead citrate to be thermally decomposed into lead oxide, which will not explode when dissolved in lead nitrate, thereby improving safety;

[0030] (5) The solvent used in the lead nitrate solution purification step of the present invention removes heavy metal impurities in the plating solution and improves the purity of the plating solution. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.

[0032] Example 1: A method for recycling waste titanium mesh lead dioxide anode plates, the specific steps are as follows:

[0033] (1) Pretreatment of waste anode plates: The waste titanium mesh lead dioxide anode plates are ultrasonically cleaned with 10 wt.% dilute sulfuric acid for 10 min to obtain pretreated waste titanium mesh lead dioxide anode plates;

[0034] (2) Electrochemical stripping of lead dioxide: The waste titanium mesh lead dioxide anode plate from step (1) was used as the anode and the aluminum plate was used as the cathode. The anode was placed in a nitric acid electrolyte at a temperature of 25°C, ultrasound, and mechanical stirring (100 rpm) at an anode current of 5 A / dm 2 Electrochemical stripping is performed at a current density of 1000 nm for 1 h to obtain a titanium mesh plate, lead dioxide particles and lead nitrate solution free of lead dioxide; the nitric acid electrolyte contains 150 g / L HNO3, 1 g / L Ce(NO3)3, 30 ml / L hydrogen peroxide (30 wt.%), 5 g / L glass microspheres and 5 g / L silicon carbide micropowder;

[0035] (3) Re-coating and assembling the titanium mesh: The titanium mesh that does not contain lead dioxide in step (2) is subjected to hot alkali washing (250° C.), and then segmented to separate the titanium mesh, titanium conductive reinforcement ribs and titanium copper-clad conductive beams; the hot alkali washing solution is a KNO3-KOH mixed solution, and the KNO3 concentration in the KNO3-KOH mixed solution is 5wt.%, and the KOH concentration is 5wt.%;

[0036] The titanium mesh is sequentially sandblasted, pickled at 80°C (with oxalic acid at a concentration of 10wt.%), washed with deionized water, and dried to obtain a pretreated titanium mesh. The pretreated titanium mesh is uniformly coated with a precursor liquid (the solvent of the precursor liquid is n-butanol, containing stannous chloride, antimony chloride, cerium chloride, calcium chloride, and dilute hydrochloric acid), dried at 80°C, and sintered at 400°C for 5 minutes. The coating-drying-sintering process is repeated 3 to 8 times, and finally calcined for 1 hour to obtain a titanium mesh bottom layer. The titanium mesh bottom layer is assembled and welded with a titanium conductive reinforcement rib and a titanium-clad copper conductive beam to obtain a titanium mesh plate containing a bottom layer. The total molar amount of stannous chloride, antimony chloride, cerium chloride, and calcium chloride in the precursor liquid is 100, and stannous chloride accounts for 72, antimony chloride accounts for 15, cerium chloride accounts for 9, and calcium chloride accounts for 4; the amount of commercially available dilute hydrochloric acid added to the precursor liquid is 20ml / L;

[0037] (4) Conversion of lead dioxide to lead oxide: in step (2), the lead dioxide particles are wet-milled at a ball milling speed of 100 rpm for 4 h (the mass ratio of lead dioxide particles, water, and zirconium dioxide is 10:10:80) to a particle size of 400-500 mesh, and dried to obtain lead dioxide powder. The lead dioxide powder is mixed evenly with citric acid and a hydrogen peroxide solution and stirred for reaction at a temperature of 50° C. for 1 h. The solid is separated from the liquid, and the solid is lead citrate. The lead citrate is calcined and decomposed at a temperature of 300° C. for 1 h to obtain lead oxide. The molar ratio of the lead dioxide powder, citric acid, and the hydrogen peroxide solution is 20:70:10.

[0038] (5) Purification of lead nitrate solution: dissolving the lead oxide prepared in step (4) in the lead nitrate solution prepared in step (2), adding 3 ml / L of commercially available hydrogen peroxide, and then adding sodium hydroxide to adjust the pH value to 1 for precipitation reaction, solid-liquid separation, adding 1 g / L of Na2S to the filtrate for reaction, solid-liquid separation to obtain a base plating solution, adding copper nitrate to the base plating solution, and adding dilute nitric acid to adjust the pH value to 1 to obtain a lead nitrate plating solution; the lead nitrate plating solution contains 200 g / L of lead nitrate, 0.1 g / L of copper nitrate, 5 g / L of nitric acid, and 0.05 g / L of sodium fluoride;

[0039] (6) Electrodeposition of lead dioxide: The titanium mesh plate containing the bottom layer in step (3) is placed in the lead nitrate plating solution in step (5) at a temperature of 50° C. and an anode current density of 100 A / dm 2 Electrodeposition was performed for 3 h to obtain a titanium mesh lead dioxide anode plate;

[0040] The titanium mesh lead dioxide anode plate of this embodiment has good electrode conductivity and low cell voltage during electrolysis. The recovery rate of waste titanium mesh lead dioxide anode plates reaches more than 85%. Compared with the waste plates, the lead dioxide on the redeposited titanium mesh lead dioxide anode plates is dense and free of pores, and the service life of the plates is long.

[0041] Embodiment 2: A method for recycling waste titanium mesh lead dioxide anode plates, the specific steps are as follows:

[0042] (1) Pretreatment of waste anode plates: The waste titanium mesh lead dioxide anode plates are ultrasonically cleaned with 30 wt.% dilute sulfuric acid for 30 min to obtain pretreated waste titanium mesh lead dioxide anode plates;

[0043] (2) Electrochemical stripping of lead dioxide: The waste titanium mesh lead dioxide anode plate from step (1) was used as the anode and the aluminum plate was used as the cathode. The anode was placed in a nitric acid electrolyte at a temperature of 40°C, ultrasound, and mechanical stirring (300 rpm) at an anode current of 30 A / dm 2 Electrochemical stripping is performed at a current density of 6000 nm for 6 hours to obtain a titanium mesh plate, lead dioxide particles and lead nitrate solution free of lead dioxide; the nitric acid electrolyte contains 350 g / L HNO3, 5 g / L Ce(NO3)3, 100 ml / L hydrogen peroxide (30 wt.%), 10 g / L glass microspheres and 10 g / L silicon carbide micropowder;

[0044] (3) Re-coating and assembling the titanium mesh: The titanium mesh that does not contain lead dioxide in step (2) is subjected to hot alkali washing (400° C.), and then segmented and separated into the titanium mesh, titanium conductive reinforcement ribs and titanium copper-clad conductive beams; the hot alkali washing solution is a KNO3-KOH mixed solution, and the KNO3 concentration in the KNO3-KOH mixed solution is 10wt.%, and the KOH concentration is 10wt.%;

[0045] The titanium mesh is sequentially sandblasted, pickled at 100°C (with 30wt.% oxalic acid), washed with deionized water, and dried to obtain a pretreated titanium mesh. The pretreated titanium mesh is uniformly coated with a precursor liquid (the solvent of the precursor liquid is n-butanol, containing stannous chloride, antimony chloride, cerium chloride, calcium chloride, and dilute hydrochloric acid), dried at 100°C, and then sintered at 600°C for 10 minutes. The coating-drying-sintering process is repeated 8 times, and finally calcined at 600°C for 2 hours to obtain a titanium mesh bottom layer. The titanium mesh bottom layer is assembled and welded with titanium conductive reinforcement ribs and titanium-clad copper conductive beams to obtain a titanium mesh plate containing a bottom layer. The total molar amount of stannous chloride, antimony chloride, cerium chloride, and calcium chloride in the precursor liquid is 100, of which stannous chloride accounts for 90, antimony chloride accounts for 5, cerium chloride accounts for 3, and calcium chloride accounts for 2; the amount of commercially available dilute hydrochloric acid added to the precursor liquid is 40ml / L;

[0046] (4) Conversion of lead dioxide to lead oxide: The lead dioxide particles in step (2) were wet-milled at a ball milling speed of 300 rpm for 8 h (the mass ratio of lead dioxide particles, water, and zirconium dioxide was 20:20:60) to a particle size of 1800-2000 mesh, and dried to obtain lead dioxide powder. The lead dioxide powder was mixed evenly with citric acid and hydrogen peroxide solution and stirred at a temperature of 80° C. for reaction for 3 h.

[0047] Solid-liquid separation, the solid is lead citrate, the lead citrate is calcined and decomposed at a temperature of 500° C. for 3 hours to obtain lead oxide; the molar ratio of the lead dioxide powder, citric acid and hydrogen peroxide solution is 40:40:20;

[0048] (5) Purification of lead nitrate solution: dissolving the lead oxide prepared in step (4) in the lead nitrate solution prepared in step (2), adding commercially available hydrogen peroxide in an amount of 7 ml / L, and then adding sodium hydroxide to adjust the pH value to 3 for precipitation reaction, solid-liquid separation, adding 3 g / L of Na2S to the filtrate for reaction, solid-liquid separation to obtain a base plating solution, adding copper nitrate to the base plating solution, and adding dilute nitric acid to adjust the pH value to 2 to obtain a lead nitrate plating solution; the lead nitrate plating solution contains 350 g / L of lead nitrate, 10 g / L of copper nitrate, 15 g / L of nitric acid, and 0.5 g / L of sodium fluoride;

[0049] (6) Electrodeposition of lead dioxide: The titanium mesh plate containing the bottom layer in step (3) is placed in the lead nitrate plating solution in step (5) at a temperature of 50° C. and an anode current density of 100 A / dm 2 Electrodeposition was performed for 3 h to obtain a titanium mesh lead dioxide anode plate;

[0050] The titanium mesh lead dioxide anode plate of this embodiment has good electrode conductivity and low cell voltage during electrolysis. The recovery rate of waste titanium mesh lead dioxide anode plates reaches more than 88%. Compared with the waste plates, the lead dioxide on the redeposited titanium mesh lead dioxide anode plates is dense and pore-free, and the service life of the plates is long.

[0051] Embodiment 3: A method for recycling waste titanium mesh lead dioxide anode plates, the specific steps are as follows:

[0052] (1) Pretreatment of waste anode plates: The waste titanium mesh lead dioxide anode plates are ultrasonically cleaned with dilute sulfuric acid having a concentration of 20 wt.% for 20 min to obtain pretreated waste titanium mesh lead dioxide anode plates;

[0053] (2) Electrochemical stripping of lead dioxide: The waste titanium mesh lead dioxide anode plate from step (1) was used as the anode and the aluminum plate was used as the cathode. The anode was placed in a nitric acid electrolyte at a temperature of 35°C, ultrasound, and mechanical stirring (200 rpm) at an anode current of 20 A / dm 2 Electrochemical stripping is performed at a current density of 4 h to obtain a titanium mesh plate, lead dioxide particles and lead nitrate solution free of lead dioxide; the nitric acid electrolyte contains 250 g / L HNO3, 3 g / L Ce(NO3)3, 65 ml / L hydrogen peroxide (30 wt.%), 7 g / L glass microspheres and 8 g / L silicon carbide micropowder;

[0054] (3) Re-coating and assembling the titanium mesh: The titanium mesh that does not contain lead dioxide in step (2) is subjected to hot alkali washing (330° C.), and then segmented to separate the titanium mesh, titanium conductive reinforcement ribs and titanium copper-clad conductive beams; the hot alkali washing solution is a KNO3-KOH mixed solution, and the KNO3 concentration in the KNO3-KOH mixed solution is 7wt.%, and the KOH concentration is 8wt.%;

[0055] The titanium mesh is sequentially sandblasted, pickled at 90°C (with oxalic acid at a concentration of 20wt.%), washed with deionized water, and dried to obtain a pretreated titanium mesh. The pretreated titanium mesh is uniformly coated with a precursor liquid (the solvent of the precursor liquid is n-butanol, containing stannous chloride, antimony chloride, cerium chloride, calcium chloride, and dilute hydrochloric acid), dried at 90°C, and then sintered at 500°C for 8min. The coating-drying-sintering process is repeated 6 times, and finally calcined at 500°C for 1.5h to obtain a titanium mesh bottom layer. The titanium mesh bottom layer is assembled and welded with titanium conductive reinforcement ribs and titanium-clad copper conductive beams to obtain a titanium mesh plate containing a bottom layer. The total molar amount of stannous chloride, antimony chloride, cerium chloride, and calcium chloride in the precursor liquid is 100, of which stannous chloride accounts for 80, antimony chloride accounts for 10, cerium chloride accounts for 7, and calcium chloride accounts for 3; the amount of commercially available dilute hydrochloric acid added to the precursor liquid is 30ml / L;

[0056] (4) Conversion of lead dioxide to lead oxide: The lead dioxide particles in step (2) were wet-milled at a ball milling speed of 200 rpm for 6 h (the mass ratio of lead dioxide particles, water, and zirconium dioxide was 15:15:70) to a particle size of 1200-1500 mesh, and dried to obtain lead dioxide powder. The lead dioxide powder was mixed evenly with citric acid and hydrogen peroxide solution and stirred at a temperature of 65° C. for 2 h.

[0057] Solid-liquid separation, the solid is lead citrate, the lead citrate is calcined and decomposed at a temperature of 400° C. for 2 hours to obtain lead oxide; the molar ratio of the lead dioxide powder, citric acid and hydrogen peroxide solution is 30:55:15;

[0058] (5) Purification of lead nitrate solution: dissolving the lead oxide prepared in step (4) in the lead nitrate solution prepared in step (2), adding 5 ml / L of commercially available hydrogen peroxide, and then adding sodium hydroxide to adjust the pH value to 2 for precipitation reaction, solid-liquid separation, adding 2 g / L of Na2S to the filtrate for reaction, solid-liquid separation to obtain a base plating solution, adding copper nitrate to the base plating solution, and adding dilute nitric acid to adjust the pH value to 1 to obtain a lead nitrate plating solution; the lead nitrate plating solution contains 300 g / L of lead nitrate, 5 g / L of copper nitrate, 10 g / L of nitric acid, and 0.25 g / L of sodium fluoride;

[0059] (6) Electrodeposition of lead dioxide: The titanium mesh plate containing the bottom layer in step (3) is placed in the lead nitrate plating solution in step (5) at a temperature of 65° C. and an anode current density of 300 A / dm 2 Electrodeposition was performed for 5 h to obtain a titanium mesh lead dioxide anode plate;

[0060] The titanium mesh lead dioxide anode plate of this embodiment has good electrode conductivity and low cell voltage during electrolysis. The recovery rate of waste titanium mesh lead dioxide anode plates reaches more than 92%. Compared with the waste plates, the lead dioxide on the redeposited titanium mesh lead dioxide anode plates is dense and free of pores, and the service life of the plates is long.

[0061] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A method for recycling waste titanium mesh lead dioxide anode plates, characterized in that: The specific steps are as follows: (1) The waste titanium mesh lead dioxide anode plate is ultrasonically cleaned with dilute sulfuric acid to obtain a pretreated waste titanium mesh lead dioxide anode plate; (2) using the waste titanium mesh lead dioxide anode plate from step (1) as an anode and an aluminum plate as a cathode, placing them in a nitric acid electrolyte, and electrochemically stripping them for 1 to 6 hours at a temperature of 25 to 40° C., under ultrasonic and mechanical stirring conditions to obtain a titanium mesh plate free of lead dioxide, lead dioxide particles and a lead nitrate solution; the nitric acid electrolyte contains HNO3, Ce(NO3)3, hydrogen peroxide, vitrified microspheres and silicon carbide micropowder; (3) The titanium mesh plate free of lead dioxide in step (2) is subjected to hot alkali washing, and then divided and separated into titanium mesh, titanium conductive reinforcement ribs and titanium copper-clad conductive beams. The titanium mesh is sequentially subjected to sandblasting, pickling, deionized water washing and drying to obtain a pretreated titanium mesh. The pretreated titanium mesh is evenly coated with a precursor liquid, dried and then sintered. The coating-drying-sintering process is repeated 3 to 8 times, and roasted for 1 to 2 hours to obtain a titanium mesh bottom layer. The titanium mesh bottom layer is assembled and welded with the titanium conductive reinforcement ribs and the titanium copper-clad conductive beams to obtain a titanium mesh plate containing a bottom layer; the solvent of the precursor liquid is n-butanol, and contains stannous chloride, antimony chloride, cerium chloride, calcium chloride and dilute hydrochloric acid; (4) the lead dioxide particles in step (2) are wet-milled to a particle size of 400 to 2000 mesh, dried to obtain lead dioxide powder, the lead dioxide powder is uniformly mixed with citric acid and hydrogen peroxide solution and reacted to obtain lead citrate, and the lead citrate is calcined and decomposed to obtain lead oxide; (5) dissolving the lead oxide prepared in step (4) in the lead nitrate solution prepared in step (2), adding hydrogen peroxide, adjusting the pH value to 1-3 with sodium hydroxide and precipitating, separating the solid from the liquid, adding Na2S to the filtrate for reaction, separating the solid from the liquid to obtain a base plating solution, adding copper nitrate to the base plating solution, and adjusting the pH value to 1-2 with dilute nitric acid to obtain a lead nitrate plating solution; (6) placing the titanium mesh plate containing the bottom layer in step (3) in the lead nitrate plating solution in step (5), and electroplating at a temperature of 50 to 80° C. for 3 to 8 hours to obtain a titanium mesh lead dioxide anode plate.

2. The method for recycling waste titanium mesh lead dioxide anode plates according to claim 1, characterized in that: The concentration of dilute sulfuric acid in step (1) is 10 to 30 wt.%.

3. The method for recycling waste titanium mesh lead dioxide anode plates according to claim 1, characterized in that: Step (2) HNO3 150-350 g / L, Ce(NO3)3 1-5 g / L, 30 wt.% hydrogen peroxide 30-100 ml / L, glass microspheres 5-10 g / L, silicon carbide powder 5-10 g / L in nitric acid electrolyte.

4. The method for recycling waste titanium mesh lead dioxide anode plates according to claim 1, characterized in that: The current density of step (2) electrochemical stripping is 5 to 30 A / dm 2 .

5. The method for recycling waste titanium mesh lead dioxide anode plates according to claim 1, characterized in that: The washing liquid for hot alkali washing in step (3) is a KNO3-KOH mixed solution, the KNO3 concentration in the KNO3-KOH mixed solution is 5-10wt.%, the KOH concentration is 5-10wt.%, the hot alkali washing temperature is 250-400°C, and the time is 3-5min; The pickling solution is an oxalic acid solution, the concentration of the oxalic acid solution is 10-20wt.%, and the pickling temperature is 80-100°C; Taking the total molar amount of stannous chloride, antimony chloride, cerium chloride and calcium chloride in the precursor liquid as 100, stannous chloride is 72-90, antimony chloride is 5-15, cerium chloride is 3-9, and calcium chloride is 2-4; the amount of dilute hydrochloric acid added to the precursor liquid is 20-40 ml / L; Each sintering temperature is 400-600°C, and the time is 5-10 minutes; the roasting temperature is 400-600°C.

6. The method for recycling waste titanium mesh lead dioxide anode plates according to claim 1, characterized in that: In step (4), the molar ratio of lead dioxide powder, citric acid and hydrogen peroxide solution is (20-40):(10-20):(40-70).

7. The method for recycling waste titanium mesh lead dioxide anode plates according to claim 1, characterized in that: The calcination decomposition temperature of step (4) is 300-500° C. and the time is 1-3 hours.

8. The method for recycling waste titanium mesh lead dioxide anode plates according to claim 1, characterized in that: In step (5), the amount of hydrogen peroxide added is 3-7 ml / L, and the amount of Na2S added is 1-3 g / L.

9. The method for recycling waste titanium mesh lead dioxide anode plates according to claim 1, characterized in that: The lead nitrate plating solution in step (5) contains 200-350 g / L of lead nitrate, 0.1-10 g / L of copper nitrate, 5-15 g / L of nitric acid, and 0.05-0.5 g / L of sodium fluoride.

10. The method for recycling waste titanium mesh lead dioxide anode plates according to claim 1, characterized in that: The anode current density of step (6) electrodeposition is 100 to 500 A / dm 2 .

Citation Information

Patent Citations

  • Method for manufacturing and repairing titanium anode coating

    CN109321956A

  • Method for recovery and reusing of etching liquid containing copper ions and nitrate

    CN109868476A

  • Method of recovering metal lead by reducing waste lead dioxide

    CN113089024A

  • Method for recovering lead

    JP2008081799A